Pemetaan Daya Saing Produk Industri Kreatif di Sumatera Barat - Ainun Mardiah; Desvi Emti; Sehani Sehani; Ratna Dewi (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
This research aims to determine the level of economic competitiveness through competitive sectors based on shift-share analysis, leading sectors based on Location Quotient analysis, creative industry mapping, and creative industry product potential in West Sumatra. This research is field research using survey methods. The approach method uses a quantitative and qualitative descriptive approach. The research results show that based on the results of the shift-share analysis there are seven competitive sectors, namely wholesale and retail trade sector, followed by construction, educational services, mining and quarrying, government administration, provision of accommodation and food and drink, services others, while tourism has not been able to compete. Based on the results of the Location Quotient analysis, there are 13 basic and superior business sectors, and the tourism sector which is among the most basic or superior sectors in West Sumatra. The results of mapping the creative industries in West Sumatra showed that Tanah Datar is the area with the most creative workers. Most of the creative industry potential in culinary businesses and is located in Tanah Datar, Pesisir Selatan, Payakumbuh, Padang Panjang, South Solok, Solok, Sinjunjung, Limapuluh Kota, Dharmasraya, Pariaman Districts.